2023
DOI: 10.1002/tcr.202300037
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electrophilic Radical Perfluoroalkylation of Electron‐Deficient Olefins

Abstract: Fluorinated organic compounds have attracted significant attention over the past few decades owing to their unique properties and versatility. An established method for the synthesis of fluorinated organic compounds involves radical perfluoroalkylation reactions towards double bonds. In this radical pathway, electrophilic perfluoroalkyl radicals exhibit excellent reactivity towards electron‐rich olefins. Therefore, several splendid perfluoroalkylation reactions of electron‐rich olefins have been reported. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…of substrates 1 h – 1 p , respectively. Reactions with low yields ( 1 h – 1 p ) demonstrated the existence of a residual substrate [10] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…of substrates 1 h – 1 p , respectively. Reactions with low yields ( 1 h – 1 p ) demonstrated the existence of a residual substrate [10] …”
Section: Resultsmentioning
confidence: 99%
“…Reactions with low yields (1 h-1 p) demonstrated the existence of a residual substrate. [10] Subsequently, the investigation on the reaction of styrenes [8] favorably showed its applicability to unsubstituted styrenes Scheme 2. Scope of conjugated olefins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reactions were performed under the argon atmosphere. 1 H, 13 C, and 19 F NMR spectra were recorded on a JEOL GSX-400 spectrometer (Jeol, Akishima, Tokyo, Japan) Scheme 4. Proposed mechanism for hydroxy-and hydro-perfluoroalkylation.…”
Section: General Informationmentioning
confidence: 99%
“…Indeed, many examples of perfluoroalkylation to electron-rich olefins have been reported. However, few studies have reported on perfluoroalkylation with conjugated olefins [13], particularly styrene, due to the likelihood of side reactions such as oligomerization, polymerization, and nucleophilic trapping.…”
Section: Introductionmentioning
confidence: 99%